Electrochemical Behavior of Ferritic Stainless Steel Alloyed with 1 wt% Ti, V, and Nb in Hydrochloric Acid Solution - Demiroren, H.; Aksoy, M. (Natl Assoc Corrosion Eng, 2009)
Electrochemical impedance spectroscopy (EIS) is a powerful, rapid, and accurate nondestructive method for the evaluation of a wide range of materials. In this work. the corrosion behavior of some ferritic stainless steels was studied in 0.3 M hydrochloric acid (HCl) acid solution. The samples were obtained from casting and forging. Stainless steels were unalloyed and alloyed with about 1 wt% Ti. V, and Nb. The steels were exposed to different heat treatments, but heat treatment was not applied to the first group samples. The second and third group samples were rapidly cooled after annealing at 1,100 degrees C for 30 min and 180 min, respectively. Corrosion resistance was calculated using the Stearn-Geary equation, and scanning electron microscopy (SEM) was performed. According to electrochemical impedance spectroscopy (EIS), the corrosion resistance increased by the alloying element. Heat treatment has a critical effect on the corrosion resistance. The best corrosion resistance was observed from ferritic stainless steel with Nb-exposed homogenization for 180 min.
Keywords: alloying element; corrosion; corrosion resistance; electrochemical impedance spectroscopy; ferritic stainless steel; heat treatment